Permissibility of Family Planning in Islam - Ali Miqdad Ali; Musa-Jeje Ibrahim Aladire (Penerbit Hellow Pustaka, 2024)
This research delves into the nuanced perspective within Islamic teachings regarding the permissibility of family planning. Acknowledging the importance of family in Islam, the study aims to explore the religious and ethical considerations surrounding family planning practices within the context of Islamic jurisprudence. The research employs a multidisciplinary approach, integrating textual analysis of Quranic verses and Hadiths with a review of scholarly interpretations and contemporary Islamic jurisprudential discussions. Furthermore, qualitative interviews and surveys are conducted among Islamic scholars, community leaders, and practitioners to capture diverse perspectives and experiences related to family planning in Islamic communities. The findings of the study reveal a spectrum of opinions within the Islamic community regarding family planning, with some scholars emphasizing the importance of procreation while others advocate for responsible family planning within the framework of Islamic ethics. In conclusion, this research offers insights into the permissibility of family planning in Islam by navigating through traditional Islamic sources and contemporary discussions. The findings contribute to a nuanced understanding of family planning within the Islamic context and provide valuable perspectives for both scholars and practitioners seeking guidance on this complex and vital aspect of family life in Muslim communities.